Common themes and unique proteins for the uptake and trafficking of nickel, a metal essential for the virulence of Helicobacter pylori - De Reuse, Hilde; Vinella, Daniel; Cavazza, Christine (Frontiers in Cellular and Infection Microbiology, 2013)
Nickel is a virulence determinant for the human gastric pathogen Helicobacter pylori. Indeed, H. pylori possesses two nickel-enzymes that are essential for in vivo colonization, [NiFe] hydrogenase and urease, an abundant virulence factor that contains 24 nickel ions per active complex. Because of these two enzymes, survival of H. pylori relies on an important supply of nickel, implying a tight control of its distribution and storage. In this review, we will present the pathways of activation of the nickel enzymes as well as original mechanisms found in H. pylori for the uptake, trafficking and distribution of nickel between the two enzymes. These include (i) an outer-membrane nickel uptake system, the FrpB4 TonB-dependent transporter, (ii) overlapping protein complexes and interaction networks involved in nickel trafficking and distribution between urease and hydrogenase and, (iii) Helicobacter specific nickel-binding proteins that are involved in nickel storage and can play the role of metallo-chaperones. Finally, we will discuss the implication of the nickel trafficking partners in virulence and propose them as novel therapeutic targets for treatments against H. pylori infection.